2020
DOI: 10.1681/asn.2020030326
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Expressed Single Nucleotide Variation and Single Cell RNA Sequencing To Define Immune Cell Chimerism in the Rejecting Kidney Transplant

Abstract: BackgroundIn solid organ transplantation, donor-derived immune cells are assumed to decline with time after surgery. Whether donor leukocytes persist within kidney transplants or play any role in rejection is unknown, however, in part because of limited techniques for distinguishing recipient from donor cells.MethodsWhole-exome sequencing of donor and recipient DNA and single-cell RNA sequencing (scRNA-seq) of five human kidney transplant biopsy cores distinguished immune cell contributions from both participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 33 publications
13
82
0
Order By: Relevance
“…A recent study analyzed immune cell chimerism during kidney transplant rejection in humans (13). In these studies, the authors showed using single cell RNA sequencing that a population of macrophages expressing C1QC and CD81 was maintained in the donor kidney for several days/weeks post-transplant when the kidney was not undergoing rejection (13). In contrast, the authors also showed that the number of donor macrophages was significantly reduced as the kidneys underwent rejection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study analyzed immune cell chimerism during kidney transplant rejection in humans (13). In these studies, the authors showed using single cell RNA sequencing that a population of macrophages expressing C1QC and CD81 was maintained in the donor kidney for several days/weeks post-transplant when the kidney was not undergoing rejection (13). In contrast, the authors also showed that the number of donor macrophages was significantly reduced as the kidneys underwent rejection.…”
Section: Discussionmentioning
confidence: 99%
“…6D and Fig. S12A), (60). We found a cell population that is highly enriched for genes expressed in mouse damage-associated PT cells, including SOX9, VCAM1, and CDH6.…”
Section: Damage-associated Pt Cells Exhibit High Ferroptotic Stress After Severe Irimentioning
confidence: 71%
“…Among macrophage subtypes, infiltrating Ly6C hi Chil3 + macrophage and Ly6C lo patrolling macrophages are commonly found in normal kidneys (16,42), whereas IFNIC and Mrc1 + macrophages are more common to disease models like unilateral ureteric obstruction model (42). Study of kidney allograft biopsies from human recipients undergoing AR and CR also identified immune populations like those in mice, including monocytes, B cells, T cells, plasma cells (43)(44)(45), therefore independently supporting a role of these cells in kidney rejection in humans. However, due to the limited size of human biopsy samples and the large percentage of parenchymal cells, further analysis of immune cell subtypes is lacking.…”
Section: Discussionmentioning
confidence: 99%